A185 EUS-GUIDED LUMEN-APPOSING METAL STENT PLACEMENT SHOULD BE THE PREFERRED ENDOSCOPIC TREATMENT FOR ACUTE CHOLECYSTITIS IN A NON-SURGICAL PATIENT. (15th March 2019) - Kok, B; Sandha, G S
Abstract: Background: Endoscopic ultrasound-guided transmural gallbladder (GB) drainage (EUS-GBD) for the non-surgical management of acute cholecystitis has been shown to be safe and effective compared with percutaneous cholecystostomy (PC). The recent use of lumen-apposing metal stents (LAMS) for EUS-GBD is an emerging approach that may be associated with improved outcomes. Aims: We describe a case of EUS-GBD with a LAMS for acute cholecystitis in a non-surgical patient. Methods: Retrospective review of case history. Results: A 73-year-old female presented with abdominal pain and jaundice. Abdominal ultrasound revealed cholelithiasis and a dilated common bile duct (CBD). ERCP confirmed a CBD stone which was extracted after sphincterotomy. In view of extensive comorbidity, she was deemed high-risk for cholecystectomy. She re-presented 1 month later with clinical and ultrasound features of acute cholecystitis. Urgent PC was performed with clinical resolution. Cholecystography during period of PC indwell, however, indicated that her cystic duct remained obstructed. After removal of the PC at 6 weeks, she was re-admitted with acute cholecystitis and a dilated GB confirmed on CT scan. Multidisciplinary consensus suggested that endoscopic cholecystenterostomy would be the best treatment option given the high surgical risk and failure of prior PC. EUS-GBD was carried out under conscious sedation. Once the distended gallbladder was optimally located, a trans-duodenal approach was used for the placement of a 10mm x 15mm LAMS (Hot AXIOS, Boston Scientific Corporation, Marlborough, MA, USA). Immediately, there was drainage of murky bile and small stones into the duodenum. The procedure time was 12 minutes. CT scan the next day confirmed decompression of the gallbladder (see figure) with clinical (relief of pain) and biochemical (normalization of leukocytosis) resolution within 24 hours. She was discharged 4 days after EUS-GBD. Conclusions: The use of a LAMS for EUS-GBD is safe and effective. It is also technically easier to place and should be considered as the preferred modality for the endoscopic treatment of acute cholecystitis in a non-surgical patient. Funding Agencies: None